Project-Based Learning-Oriented Worksheet Based on Local Wisdom and Green Chemistry - Hakim, Fachri (Chemistry Education Department, 2024)
This study aims to determine the feasibility of worksheets and the science process skills of students using worksheets based on local wisdom-oriented projects in Central Java, with insights from green chemistry. The research follows the Research and Development (RD) methodology, specifically the modified 4D development procedure, which includes define, design, and develop stages. The study was conducted at UIN Walisongo Semarang with 60 chemistry education students participating. Expert validation results indicated that the worksheet, based on local wisdom-oriented projects with green chemistry insight, was feasible, achieving a validity percentage of 86.53%, categorized as very valid. Observations of students’ science process skills using project worksheets 1, 2, and 3 yielded an average score of 78.6%. Pretest and post-test data on students' science process skills showed scores of 29.8 and 70.5 for the experimental class, and 29.64 and 54.46 for the control class, respectively. The average n-gain score for the experimental class was calculated to be 58%, indicating it falls within the moderately effective category. In conclusion, the worksheet, which leverages the local wisdom of Central Java and incorporates green chemistry principles into the study of acid-base material, is feasible and can be effectively used as a learning resource for students.